Behavioral Bias and Investment Decisions: A Moderating Role of Financial Literacy on Individual Investors of Nepal - Duwal, Bal Ram; Damai, Sital; Bhatta, Sheena (International Research Journal of MMC, 2026)
Purpose: The objective of the study was to examine the influence of behavioral biases (overconfidence, herding bias, disposition effect) on individual investment choices. The study explored the relationship between financial literacy and investment decisions, and whether financial literacy moderated the relationship between behavioral biases and investment decisions. Methods: The study used a descriptive cross-sectional analytical research design, where primary data were gathered using a structured questionnaire based on a five-point Likert scale. The questionnaire was administered in both an online format, developed by link (Google Forms), and as a physical questionnaire to the investors who trade in a variety of securities listed in the Nepal Stock Exchange (NEPSE). Using a convenience sampling method, responses from 235 participants were collected. The data were analyzed through Partial Least Squares Structural Equation Modelling with SMART-PLS 4 software. Findings: The results revealed a significant relationship between behavioral biases (disposition effect, herding bias, and overconfidence bias) and investment decision-making. A significant relationship between financial literacy and investment decisions was found. The study found that financial literacy did not moderate the relationship between overconfidence bias, herding bias, disposition effect, and investment decisions. Implications: The findings suggest that financial literacy programs in Nepal should integrate behavioral finance principles and emphasize experiential learning to help investors recognize and manage biases. Tailored initiatives addressing gender, age, and experience differences can enhance effectiveness. Regulators like SEBON should improve market transparency and promote long-term investment incentives to reduce speculative and emotionally driven decisions. Research Ethics: Informed consent from the survey participants was collected by making them aware of their role in the survey, the research purpose, procedure, and use of data gathered. To uphold confidentiality, the survey-maintained anonymity and did not ask for personal information.